Applications of Nanotechnology in Treating Infections Caused by Multidrug Resistance Bacteria (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Nanotechnology is increasingly being used for therapeutic applications, particularly as a new paradigm for infectious diseases. Infections caused by multidrug-resistant organisms (MDROs) are becoming a major source of morbidity and mortality around the world. Antibiotic choices for infections caused by MDROs are frequently restricted. These clinical issues underline the crucial need for alternate and effective antibacterial treatments. Nanoparticles (NPs) can penetrate the cell membrane of pathogenic microbes and disrupt critical molecular processes, resulting in novel antibiotic actions. NPs have proven synergy when combined with appropriate antibiotics and may help to prevent the global challenge of growing bacterial resistance. In this review, we summarized current studies on the broad classification of NPs that have shown in vitro antibacterial action against MDROs, including the Pathogens associated with (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) ESKAPE.The pharmacokinetics and pharmacodynamic properties of NPs, as well as bacterial resistance mechanisms to NPs, were also discussed.